Bertumbuh dan Berakar dalam Kristus: Kursus Teologi Warga Gereja (KTWG) sebagai Upaya Penguatan Jemaat di Resort GKE Kahayan Hulu - Idrus Sasirais; Sanon; Sudianto (Akoloutheo: Jurnal Pengabdian Kepada Masyarakat, 2025)
This article presents the outcomes of a community engagement initiative conducted through the Church Members’ Theology Course (Kursus Teologi Warga Gereja, KTWG), held at the GKE Kahayan Hulu Resort on 15 February 2025. The program was attended by 41 participants, comprising pastors, church council members, and congregants representing 11 local churches within the resort. Employing a qualitative approach through lectures, group discussions, and interactive sessions, the course aimed to deepen the theological understanding of church members. Three central themes were explored: Christian theology concerning work, money, and material possessions; pastoral spirituality; and the proclamation of the Gospel in the digital age. The results indicate a heightened awareness among participants regarding the role of faith in everyday life, the significance of pastoral spiritual integrity, and the urgency of contextual evangelism through digital media. Participant responses reflected strong appreciation, emphasizing the relevance of the themes to their spiritual and social realities. This initiative underscores the importance of theological education for church members as a means of fostering growth and rootedness in faith in Christ, bridging academic theology with congregational life, and strengthening the resilience of Christian communities in Kalimantan.